Cross layer design of interference aware multi-hop mobile relay wimax network - Dzulkurnain, Muhammad Firdaus (2011)
The MMR (IEEE 802.16j) WiMAX standard provides a mechanism for creating multi-hop relay, which can extend coverage and capacity and be deployed as a high speed wide area wireless network. Interference in wireless system is one of the most significant factors that limit the network capacity and scalability of wireless relay networks. Cross layer design (CLD) and optimization is known to improve the performance of wireless communication and mobile networks. In order to design a spectrally efficient IEEE 802.16j relay network, a joint design and optimization technique that relies on Physical layer which has the interference information, as well as scheduling and route selection mechanism in Data Link layer will be opted using software NCTUns and programming languange. The proposed scheme includes a novel interference-aware route construction algorithm and an enhanced scheduling scheme, which consider both traffic load and demand interference conditions. This interference-aware design should lead to better spatial reuse and thus higher spectral efficiency. By taking average 10 mobile users into consideration, the results show that the throughput is enhanced up to 8.5% from the normal implementation. It can be concluded that, the CLD approach will select the best route selection based on the SNR calculation and improve the scheduling for this network